Consensus statement for the treatment of infantile haemangiomas with propranolol. (1st March 2017) - Smithson, Sarah L; Rademaker, Marius; Adams, Susan; Bade, Stuart; Bekhor, Philip; Davidson, Samantha; Dore, Amanda; Drummond, Catherine; Fischer, Gayle; Gin, Alexander; Grills, Claire; Halbert, Anne; et al.
Abstract: Although most infantile haemangiomas do not require treatment due to a natural history of spontaneous involution, some require early intervention. The Australasian Vascular Anomalies Network and the Australasian Paediatric Dermatology Network have developed a consensus statement for the treatment of infantile haemangiomas with oral propranolol. Infants with haemangiomas that are life threatening, at risk of ulceration, or at risk of causing a significant functional impairment, psychological impact or physical deformity should be treated early with oral propranolol. Oral propranolol is safe and effective and in most healthy infants oral propranolol can be started in an outpatient setting.